Non-islet Cell Hypoglycemia: Case Series and Review of the Literature - Garla, Vishnu; Sonani, Hardik; Palabindala, Venkatraman; Gomez-Sanchez, Celso; Subauste, Jose; Lien, Lillian Francis (Frontiers in Endocrinology, 2019)
Non islet cell hypoglycemia (NICH) is hypoglycemia due to the overproduction of insulin like growth factor-2 (IGF-2) and its precursors which can activate the insulin receptor. Typically, large mesenchymal and epithelial tumors can cause NICH. Diagnosis is confirmed by finding an elevated IGF-2/IGF-1 ratio. The mainstay of treatment is surgical excision. Glucocorticoids may be used in cases where surgery is not possible. We present two cases of NICH with different outcomes. A 33 year old male patient admitted with altered mental. He was found walking naked outside his house. Laboratory assessment revealed severe hypoglycemia. Further evaluation showed low levels of insulin, C-peptide, and beta-hydroxy butyrate along with an elevated IGF-2/IGF-1 ratio confirming the diagnosis of NICH. Computed tomography (CT) of the abdomen showed a massive tumor of the liver consistent with hepatocellular carcinoma. Since the patient refused surgery, he was started on prednisone however the hypoglycemia persisted. A 54 year old female patient with a history of type 2 diabetes mellitus (DM) who started experiencing hypoglycemia. Despite stopping her insulin she continued to have hypoglycemia necessitating the administration of high concentrations of intravenous dextrose. Further evaluation showed low levels of insulin, C-peptide, and beta-hydroxy butyrate along with an elevated IGF-2/IGF-1 ratio consistent with the diagnosis of NICH. CT abdomen showed a 24 cm tumor near the uterus. Biopsy was consistent with a gastrointestinal stromal tumor (GIST). Surgical excision was done and the hypoglycemia resolved.